Developing Student's Islamic Character through the Madrasah Diniyah Program at MTsN 16 Jombang - Syarifah; Putri Adinda Ayudiyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The phenomenon of moral decline among adolescents, such as decreasing discipline, weakening manners, and inconsistency in religious practices, poses a serious challenge for Islamic educational institutions. This condition highlights the need for religious development programs capable of internalizing Islamic values in a sustainable manner. This study aims to analyze the development of students’ Islamic character through the Madrasah Diniyah Program at MTsN 16 Jombang. This research employed a descriptive qualitative approach, with data collection techniques in the form of field observation, semi-structured interviews, documentation. The data were analyzed using content analysis procedures, including data reduction, data display, and conclusion drawing. The findings indicate that the Madrasah Diniyah Program at MTsN 16 Jombang is implemented in a structured manner through Qur’anic learning, tahfiz programs, and classical Islamic text studies integrated with the madrasah’s religious culture. The program contributes positively to the development of students’ Islamic character, particularly in terms of discipline, responsibility, noble character, and religiosity. Therefore, the Madrasah Diniyah Program plays an important role in strengthening Islamic character education within the madrasah context.